Through Thickness Microstructural and Texture Inhomogeneity Within Al Layers in ARB-Produced Al-Al(Sc) Layered Composite Sheets - Najafzadeh, N.; Quadir, Md Zakaria; Munroe, P. (2015)
© 2015, The Minerals, Metals & Materials Society and ASM International.Alternatively layered composite sheets of commercially pure (99.8 pct purity) aluminum and an Al-0.3wtpctSc alloy (either in the supersaturated solid solution or age-hardened conditions) were generated through accumulative roll bonding for up to 5 cycles. The transverse sections of the sheets were examined to investigate the microstructure and texture inhomogeneities developed during the rolling process. Electron backscatter diffraction and transmission electron microscopy was used for this investigation. It was found that an inhomogeneous microstructure and texture was developed through the aluminum layers of the sheet thickness. The nature of inhomogeneities changes as the ARB bonding progresses to higher cycles. Microstructural inhomogeneities remain prominent in the first ARB cycle and diminish during the subsequent cycles. Texture inhomogeneities appear in different forms as rolling progresses. High frictional shear forces in the surface and in-plane shear forces across bonding interfaces derive these inhomogeneities.